Done with slavery : the Black fact in Montreal, 1760-1840 - Mackey, Frank (Studies on the history of Quebec ;, 2010)
"Through close examination of archival and contemporary sources, Mackey uncovers largely unknown aspects of the black transition from slavery to freedom. While he considers the changing legal status of slavery, much of the book provides a detailed and nuanced reconstruction of the circumstances of black Montrealers and their lived experience. The resulting picture is remarkably complex, showing the variety of occupations held by blacks, the relationships they had with those they served, their encounters with the judicial and political systems, and the racial mingling that came with intermarriage and apprenticeships. Done with Slavery casts the categories of blackness and slavery in a new light, showing that broad histories of the phenomenon must begin to take into account the specifics of the lives of "marginal" black populations."--Publisher Description